JULA-JULI (Ujung Serving – Ujung Peduli) ACTION PROGRAM INNOVATION IN UJUNG KOTA SUB-DISTRICT OF SURABAYA - Wahyudi Hardiyanto; Amirul Mustofa (Halu Oleo University, 2025)
The Jula-Juli Action Program (Ujung Melayani – Ujung Peduli) is a public service innovation applied in Ujung Village, Surabaya. The program combines administrative services with social initiatives such as assistance for vulnerable groups, skills training, and increased citizen solidarity, with a technology-based approach and community participation. This study aims to analyse the effectiveness of the Jula-Juli Action Program in improving the quality of public services and empowering the community in Ujung Village. This study uses a descriptive method with a qualitative approach through surveys, participatory observations, and document analysis. The Diffusion of Innovations Theory by Everett M. Rogers is used to analyse the level of public awareness, perception of benefits, readiness for adoption, and the influence of the social environment on the implementation of these programs. The results of the July-July Action Program in Ujung Village show significant success in improving the quality of public services and community empowerment. The increase in the efficiency of administrative services is reflected in the ease of access and better transparency, which contributes to a drastic reduction in complaints about services. In addition, this program has succeeded in strengthening social solidarity through various care-based activities, such as skills training and assisting vulnerable groups. While challenges remain, such as information access gaps and resistance to technology, participatory strategies and technology-based approaches have been able to overcome them gradually. Solutions for program sustainability require strategies to increase human resource capacity, diversify funding, and strengthen cross-sector collaboration.